Non-invasive assessment of liver fibrosis and prognosis: an update on serum and elastography markers. (3rd April 2019) - Agbim, Uchenna; Asrani, Sumeet K.
ABSTRACT: Introduction : Non-invasive assessment of fibrosis is increasingly utilized in clinical practice to diagnose hepatic fibrosis. Non-invasive assessment of liver fibrosis relies on biologic and/or physical properties to assess tissue fibrosis. Serum markers estimate fibrosis by incorporating markers reflecting hepatic function (indirect markers) and/or markers measuring extracellular matrix degradation/fibrogenesis (direct markers). Radiology based techniques relay the mechanical properties and stiffness of a tissue, with increased stiffness associated with more advanced fibrosis. Areas covered : In this comprehensive review, the recent literature discussing serum markers and elastography-based techniques will be covered. These modalities are also explored in the setting of various liver diseases. Expert opinion : The etiology of liver disease and clinical context should be taken into consideration when non-invasive markers are incorporated in clinical practice. Non-invasive assessment of fibrosis has been most extensively utilized in hepatitis C, followed by hepatitis B and nonalcoholic fatty liver disease, but its role remains less developed in other etiologies of liver disease such as alcohol-associated liver disease and autoimmune liver disease. The role of non-invasive markers in predicting progression or regression of fibrosis, development of liver-related events and survival needs to be further explored.